Genomic Characteristics of NDM-Producing Enterobacteriaceae Isolates in Australia and Their bla(NDM) Genetic Contexts - Wailan, Alexander M. (Antimicrob Agents Chemother, 2015)
bla(NDM) has been reported in different Enterobacteriaceae species and on numerous plasmid replicon types (Inc). Plasmid replicon typing, in combination with genomic characteristics of the bacterial host (e.g., sequence typing), is used to infer the spread of antimicrobial resistance determinants between genetically unrelated bacterial hosts. The genetic context of bla(NDM) is heterogeneous. In this study, we genomically characterized 12 NDM-producing Enterobacteriaceae isolated in Australia between 2012 and 2014: Escherichia coli (n = 6), Klebsiella pneumoniae (n = 3), Enterobacter cloacae (n = 2) and Providencia rettgeri (n = 1). We describe their bla(NDM) genetic contexts within Tn125, providing insights into the acquisition of bla(NDM) into Enterobacteriaceae. IncFII-type (n = 7) and IncX3 (n = 4) plasmids were the most common plasmid types found. The IncHI1B (n = 1) plasmid was also identified. Five different bla(NDM) genetic contexts were identified, indicating four particular plasmids with specific bla(NDM) genetic contexts (NGCs), three of which were IncFII plasmids (FII-A to -C). Of note, the bla(NDM) genetic context of P. rettgeri was not conjugative. Epidemiological links between our NDM-producing Enterobacteriaceae were established by their acquisition of these five particular plasmid types. The combination of different molecular and genetic characterization methods allowed us to provide insight into the spread of plasmids transmitting bla(NDM).